Prefrontal Disinhibition in Social Fear: A Vital Action of Somatostatin Interneurons - Wang, Jun; Tian, Yuanyuan; Zeng, Ling-Hui; Xu, Han (Frontiers in Cellular Neuroscience, 2020)
Social fear and avoidance to social partners and social situations represent the core behavioral symptom of social anxiety disorder (SAD), a prevalent psychiatric disorder worldwide. The pathological mechanism of SAD remains elusive and there are no specific and satisfactory therapeutic options currently available. With the development of appropriate animal models, growing studies start to unravel neuronal circuit mechanisms underlying social fear, and underscore a fundamental role of the prefrontal cortex (PFC). Prefrontal cortical functions are implemented by a finely wired microcircuit composed of excitatory principal neurons and diverse subtypes of inhibitory interneurons (INs). Disinhibition, defined as a break in inhibition via interactions between IN subtypes that enhances the output of excitatory principal neurons, has recently been discovered to serve as an efficient strategy in cortical information processing. Here, we review the rodent animal models of social fear, the prefrontal IN diversity and their circuits with a particular emphasis on a novel disinhibitory microcircuit mediated by somatostatin-expressing INs in gating social fear behavior. The INs subtype distinct and microcircuit-based mechanism advances our understanding of the etiology of social fear and shed light on developing future treatment of neuropsychiatric disorders associated with social fear.